Oxalis section Alpinae (Oxalidaceae): orbicule diversity and pollen grain morphology - López, Alicia (2016)
Orbicule characteristics and pollen morphology were studied using light microscopy and scanning electron microscopy with 13 species of Oxalis section Alpinae, endemic to South America. Orbicules are either homogeneous or heterogeneous in size; surface smooth or with punctuations; margin smooth, lobed, or wavy; rounded, oblong, or irregular shapes; variable clustering. According to orbicule characteristics, six groups are proposed. The Oxalis pollen grain is 3-colpate and the shape is prolate spheroidal, oblate spheroidal, or spheroidal; ambit rounded or triangular. Exine microreticulate, semitectate, brochate. Brochi circular, oval, triangular to polygonal. Lumen with or without content. Sporopollenin generally forming groups that may be in rows in the margins or in the center of colpus.